Valorization of coconut (Cocos nucifera L.) testa as a biocolourant - Ramesh, S. V.; Pandiselvam, R.; Shameena Beegum, P. P.; Shil, Sandip; Sugatha, P.; Sharanya, K.; Manikantan, M. R.; Gopal, Murali; Hebbar, K. B.; Uchoi, Anok; Das, Alpana; Bhat, Ravi; et al. (Frontiers in Sustainable Food Systems, 2024)
Introduction Coconut testa, a by-product of the coconut processing industry, is currently underutilised. This study aimed to extract a coconut testa-based food colourant using various organic solvents and physical methods, and to utilise this colourant in food product preparation. Methods Different organic solvents, along with various time and temperature combinations, were employed for colourant extraction using both a laboratory-scale water bath and ultrasonication. The colour coordinate values (CIELab) of the testa-derived colourants were measured, and the colourants were screened for various phytochemicals. The in vitro antioxidant potential of the testa colourant was assessed by quantifying total phenolics, and the phytochemical composition, including monomeric anthocyanins, was evaluated. Results The study determined the optimal combinations of organic solvents, temperature and time to obtain extracts with maximum antioxidant activity and total phenolic content (TPC). Acidified ethanol-based extracts of testa colourants yielded highest polyphenol content (154.39 ± 2.63 mg GAE/g) and flavonoids content (53.65 ± 0.62 mg QE/g). Similarly, ethanol-based extractants of coconut testa produced high anthocyanin content [823.02 ± 1.81 mg Cy-3-glc equivalents (C3GE)/100 g]. Acidified (0.3 M HCl) solvents at relatively high temperature and time combinations exhibited high antioxidant potential of testa colourant, as measured by CUPRAC, FRAP, and DPPH assays. Following the foam mat drying process of the colourant, a mature coconut water-based jelly was prepared by incorporating the testa colourant extracted with acidified ethanol. Discussion This study highlights the biochemical and antioxidant potential of the food colorant derived from coconut testa and explores its suitability for functional food applications. Therefore, coconut testa extract serves a dual purpose: it enhances the aesthetic appeal of food as a colourant and provides significant health-promoting properties due to its high anthocyanin content. Insights from this study could help in promoting the valorization of one of the beneficial by products of coconut industry.